Association between occupational physical activity and quantitative bone ultrasound in sawmill workers - Cvijetić, Selma (Array, 2021)
A small number of studies have examined the relationship between bone health and level of physical load. We explored the effect of occupational physical activity on skeletal status in younger sawmill workers using ultrasonic indices of bone density. In a cross-sectional study, we measured bone density with quantitative ultrasound (QUS) in 128 sawmill workers (89 men and 39 women), mean age 39.1 +/- 10.8 years. Back strength was measured by dynamometry. Information on occupational and leisure physical activity, joint pain, education and smoking were obtained with the questionnaire. All QUS bone parameters and back strength were significantly higher in men than in women. A T score for quantitative ultrasound index (QUI) of − 2.2 or lower was found only in two men and one women. QUI did not significantly differ based on presence of parameters of physical occupational activity (carrying loads exceeding 5 kg, repetitive movements, physical exertion while working and non-sitting position at work). When controlling for age, gender and body mass index, participants with higher smoking index had significantly lower QUI (p=0.004). Physical workload was not significantly associated with QUI. In our working population, some lifestyle habits, such as smoking, had a greater impact on bone health than physical occupational activity.